Penilaian Portopolio: Portfolio Assessment - Mukin, Muh. Sulaiman Rifai Aprianus; Sunarto, Sunarto; Amien, Saiful (ITScience (Information Technology and Science), 2024)
Portfolio assessments are increasingly popular in schools to assess student performance, achievement, and development. Portfolio assessments cover many aspects of a student's abilities and skills, allowing for a more thorough assessment than conventional evaluation methods such as written tests. It is hoped that it will improve the quality of education in Indonesia and encourage more meaningful learning. This study aims to evaluate how effective portfolio assessment is in improving the quality of learning and how it impacts students' motivation and academic achievement. In addition, this study also examines how portfolio assessment can be used well in the Indonesian education system. This study analyses the literature on portfolio assessment topics, including books, scientific journals, and research reports. The research includes a theoretical review of portfolio assessment, school implementation practices, and an analysis of the advantages and problems that arise when implementing them. Literature studies show that portfolio assessments can provide a more comprehensive picture of a student's abilities and development than conventional assessment methods. Portfolio assessments also encourage students to participate more actively in learning and improve their self-reflection skills. However, to implement portfolio assessments, teachers must be trained beforehand, and assessment rubrics must be well crafted. While portfolio assessments have great potential to improve the quality of education in Indonesia by providing more thorough evaluations and encouraging meaningful learning, the success of its implementation depends on the readiness of the education system, including adequate support from schools, teachers, and education policies. Therefore, further research is needed to develop a portfolio valuation model that is in line with these commitments.